Transforming students’ green behavior through environmental education: the impact of institutional practices and policies - Cai Chen; Pomi Shahbaz; Shamsheer ul Haq (Frontiers in Psychology)
Environmental education is crucial for achieving ecological sustainability goals and transforming human behavior to promote responsible consumption. Higher education institutions play a fundamental role in transforming societies aimed at a more sustainable future through the dissemination of environmental education to millions of young people worldwide. Therefore, this study aimed to measure the role of environmental education in transforming students’ green behavior (SGB), along with other higher education institutional factors such as green campus initiatives (GCI), institutional ecosystem (IEC), institutional sustainability system (ISS), and institutional support system (ISP) through students’ green intentions (SGI). The study data were collected from 480 Chinese students enrolled in the four cities with highest number of higher education institutions through face-to-face cross-sectional survey. The collected data were analyzed through partial least squares structural equation modeling. The findings indicate a significant and positive impact of GCI, IEC, ISS, and ISP on SGI, which further positively affects the SGB. This implies that green initiatives at campus, green ecosystems, sustainable and environmentally oriented policies, and support systems of educational institutions greatly contribute to the development of students’ green intentions (SGI), which further turn into green habits fostering their green behavior. Moreover, environmental education also played a significant moderating role between SGI and SGB. The provision of support systems, organizing hands-on workshops and seminars, providing sustainable food items at cafeterias, and short campus visits focusing on campus green practices may inspire students to adopt green practices in their daily routines.